PENDAMPINGAN INOVASI PRODUK DALAM MENINGKATKAN PENJUALAN PADA UMKM JELAK JOYO FOODS BLANDONGAN PASURUAN - Licha Inabah; Dr. Suchaina, S.Pd., M.Pd.; Nanda M.H. Syahputra; Yulia Rahmawati; Muhammad Nabil Hisyam (CV SWA Anugerah, 2024)
The purpose of this study is to identify and analyze the impact of product innovation on customer satisfaction at Jelak Joyo Foods MSMEs in Blandongan, Pasuruan. Product innovation is seen as a key factor in improving customer satisfaction and daily performance, and has the potential to increase MSME stock prices. The type of analysis used is a quantitative approach using data collection techniques through surveys given to Jelak Joyo Foods customers. The data obtained through analysis using a simple regression line to reduce the relationship between product innovation variables and customer satisfaction. The results of the study indicate that product innovation has a positive and significant impact on customer satisfaction. Features such as new product features, improved product quality, and attractive packaging can have a negative impact on customer loyalty and purchase intentions. All of this suggests that Jelak Joyo Foods MSMEs need to continue to innovate to evaluate customer expectations and make effective sales in the local market. This study offers valuable insights for MSME managers in developing effective product innovation strategies to improve customer satisfaction and loyalty.